2018
DOI: 10.11144/javeriana.rgsp17-34.arfa
|View full text |Cite
|
Sign up to set email alerts
|

Adolescentes en riesgo: factores asociados con el intento de suicidio en México

Abstract: En México el suicidio ha aumentado desde hace más de cuarenta años. El objetivo fue analizar los factores asociados con el intento de suicidio en adolescentes mexicanos en tres momentos: los doce meses previos a la encuesta, antes de doce meses y en algún momento de la vida. Se ajustaron modelos de regresión logística binomial y se exploró el método del intento con un análisis de correspondencias múltiples. Las mujeres reportaron mayor prevalencia de intento de suicidio, y esta fue menor para los más jóvenes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
2
4
0
9
Order By: Relevance
“…It is important to note the higher proportion in the notifications of self-inflicted violence among female victims (79.8 %). Such findings align with the results presented by other studies (16,(28)(29)(30)(31). These findings are similar because they evidence the self-inflicted injuries that were mostly recorded in girls (18).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is important to note the higher proportion in the notifications of self-inflicted violence among female victims (79.8 %). Such findings align with the results presented by other studies (16,(28)(29)(30)(31). These findings are similar because they evidence the self-inflicted injuries that were mostly recorded in girls (18).…”
Section: Discussionsupporting
confidence: 92%
“…In England, the prevalence of self-inflicted injuries was also higher in the girls when compared to the boys (12). Added to this fact, a research study conducted in Mexico highlights higher chances of attempted suicide in female adolescents, when compared to their male counterparts (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although it did not emerge as a statistically significant factor related to suicide re-attempt, another important variable of our study was sex. Our sample was predominantly female, and this distribution is consistent with those found in other studies in which most attempts were carried out by young women [27]. Women attempt suicide three times more than men, but men die by suicide three times more than women, with some exceptions, as the article from Al-Halabi and Fonseca-Pedrero (2021) explains.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, in the study "Prevalence of the binomial anxiety and depression in male and female psychology students", it is found that the majority population was female, where the levels of anxiety and depression in men located severe level of depression 51.2 %. While anxiety in both genders presented similar percentages of 28.7 % (31). These results show that there is an exponential growth in the symptoms and the risks that this implies in the comparisons that can be made with other grades.…”
Section: Discussionmentioning
confidence: 49%